Hubungan Dakwah dan Konversi Agama : doi 10.58569/jies.v1i2.577 - Atik Dina Nasikhah (Journal of Islamic Education Studies, 2023)
This research departs from the problems that occur in the community, especially for converts. The motivation of converts in converting religion is different from one convert to another. Da'wah has an important role in the process of religious conversion. the process of religious conversion due to legalizing their marriage as well as awareness in embracing Islam. It is necessary to know the cause of this case as a basis for developing Islamic da'wah, especially for converts. For this reason, this research is important. Research data obtained through interviews. With figures related to Islamic religious guidance, observations on a number of events and research objects. Documentation related to Islamic religious guidance. The collected data is then analyzed by following the Miles and Huberman model which is divided into several stages, namely: data reduction, data presentation, data verification and conclusion drawing.Based on my findings, the motivation of converts to convert to religion is because they want to legalize their marriage, and their own desires. Da'wah provides services and understanding of Islam for converts, the process of mentoring converts is carried out by implementing religious guidance carried out for converts. The right materials and methods in the mentoring process are needed to achieve the goals of Islamic da'wah to converts.